SYSTEM OF ART THERAPEUTIC TECHNOLOGIES IN LOGOPEDIC WORK WITH VARIOUS TYPES OF SPEECH DISORDERS IN PRESCHOOL CHILDREN - Bekmanova, J.A. (SCIENCE and SOCIETY, 2026)
The article examines the system of applying art therapy technologies in corrective speech therapy work with preschool children who have various speech disorders. The theoretical foundations of using art therapy methods in speech therapy practice are analyzed, and a classification of art therapy technologies along with their differentiated application for different types of speech disorders (general speech underdevelopment, stuttering, dysarthria, alalia, rhinolalia) is presented. Practical mechanisms of the influence of isotherapy, music therapy, play therapy, and fairy tale therapy on children’s speech and psycho-emotional development are described. The results of implementing a comprehensive approach are presented, demonstrating the effectiveness of integrating art therapy methods into traditional speech therapy practice to enhance children’s motivation, reduce emotional tension, and optimize the corrective process.